PGI2 as a Regulator of Inflammatory Diseases - Stacy L. Dorris; R. Stokes Peebles (Hindawi Limited, 2012)
Prostacyclin, or PGI2, is an end product derived from the sequential metabolism of arachidonic acid via cyclooxygenase and PGI synthase (PGIS). The receptor for PGI2, IP, can be found on a variety of cell types and signaling through this receptor exhibits broad physiological effects. Historically, PGI2 has been understood to play a role in cardiovascular health, specifically having powerful vasodilatory effects via relaxation of smooth muscle and inhibiting of platelet aggregation. For these reasons, PGI2 has a long history of use for the treatment of pulmonary arterial hypertension (PAH). Only recently, its importance as an immunomodulatory agent has been investigated. PGI2 regulates both the innate and adaptive immune systems and its effects are, for the most part, thought to be anti-inflammatory or immunosuppressive in nature, which may have implications for its further clinical use.